An effective strategy to enhance the dielectric constant of organic semiconductors – CPDTTPD-based low bandgap polymers bearing oligo(ethylene glycol) side chains. Issue 3 (22nd December 2017) - Brebels, Jeroen; Douvogianni, Evgenia; Devisscher, Dries; Thiruvallur Eachambadi, Raghavendran; Manca, Jean; Lutsen, Laurence; Vanderzande, Dirk; Hummelen, Jan C.; Maes, Wouter
Abstract : Gradually increasing dielectric constants (up to 6.3) are obtained for a series of PCPDTTPD polymers. Abstract : Conjugated polymers applied in organic electronics (notably photovoltaics and photodetectors) generally exhibit relatively low dielectric constants ( ε r 3–4), which leads to significant recombination losses of photogenerated excitons. As a direct consequence, the performance of the resulting devices is inherently restricted. Some efforts have been directed toward increasing ε r of the photoactive organic compounds, but the general knowledge on the impact of specific structural variations on the dielectric constant and the final device output remains rather limited. In this study, this problem is addressed. A series of push–pull type alternating copolymers is synthesized based on 4 H -cyclopenta[2, 1- b :3, 4- b ′]dithiophene (CPDT) and 4 H -thieno[3, 4- c ]pyrrole-4, 6(5 H )-dione (TPD) subunits, with the aim to increase the dielectric constant using oligo(ethylene glycol) side chains. The amount of glycol substituents on the polymer backbone is gradually raised to systematically investigate its influence on the dielectric properties. Impedance measurements reveal a doubling of the dielectric constant (up to ε r 6.3) with respect to the reference polymer. Upon applying these materials in bulk heterojunction polymer solar cells, an efficiency of 4.4% is obtained for the best-performing device, with a particularly higher short-circuit current and improved fill factor compared to the pristine alkyl-substituted polymer. Importantly, a non-halogenated solvent – beneficial toward 'green' processing – can also be applied for the active layer deposition, affording comparable results.